2017
DOI: 10.1080/01443615.2016.1256958
|View full text |Cite
|
Sign up to set email alerts
|

Reverse breech extraction versus the standard approach of pushing the impacted fetal head up through the vagina in caesarean section for obstructed labour: A randomised controlled trial

Abstract: The objective of this study was to assess effectiveness and safety of the reverse breech extraction approach in Caesarean section for obstructed labour, and compare it with the standard approach of pushing the fetal head up through the vagina. This randomised controlled trial included 192 women. In 96, the baby was delivered by the 'reverse breech extraction approach', and in the remaining 96, by the 'standard approach'. Extension of uterine incision occurred in 18 participants (18.8%) in the reverse breech ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 16 publications
8
26
0
Order By: Relevance
“…Ideally, such a dilemma should be more adequately answered by a randomised controlled trial. However, previously reported randomised trials 8,[12][13][14] were of significantly smaller sample size. Taking into consideration the rate of failed cephalic extractions in our study, we would have expected at least a few cases in which final extraction was performed not according to randomisation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, such a dilemma should be more adequately answered by a randomised controlled trial. However, previously reported randomised trials 8,[12][13][14] were of significantly smaller sample size. Taking into consideration the rate of failed cephalic extractions in our study, we would have expected at least a few cases in which final extraction was performed not according to randomisation.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 Available data seem to favour the breech method. [8][9][10][11] A small randomised control trial of 192 women showed a significantly lower risk for maternal morbidity including uterine incision extensions, need for blood transfusion, postpartum fever, wound infection and lower rate of low Apgar score at 5 minutes using breech versus cephalic extraction. 8 Another retrospective study showed a significantly lower rate of postpartum fever and uterine incision extensions in breech extraction 9 a meta-analysis including 11 studies, 6 prospective and 5 retrospective, concluded that the overall perinatal mortality was higher in the cephalic extraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of published data demonstrating the incidence of unintended extension of uterine incision following application of reverse breech extraction (RBE) vs. abdominovaginal (AV) method. [10,18,19,20,21,22,23,24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Although this technique is widely used in different countries of the World, it is less known in Ukraine, and unfortunately almost not mentioned in Ukrainian studies and clinical protocols. All randomized clinical investigations performed in different countries demonstrated significant advantages and safety of reverse breech extraction technique (pull method) as compared with abdominovaginal (push method) [18,19,20,21] (Table I).…”
Section: Methodsmentioning
confidence: 99%